Sámi tourism in marketing material : a multimodal discourse analysis - de Bernardi, Cecilia (Acta Borealia, 2022)
The study of tourism marketing communication is an important aspect that contributes to the understanding of how destinations and locals are portrayed. Through the so-called circle of representation, images can spread from tourism marketing to other media, such as tourism photography. Marketing material in the form of 118 brochures, 3000 Instagram posts and a guidebook portraying the Sámi population mostly in Swedish Lapland, but also in Finnish Lapland as well as Finnmark, Norway, have been collected and analyzed. The focus is on pictorial and textual elements and eight previously conceptualized themes have been used to guide the analysis. The focus was on the portrayal of the Sámi Indigenous population. The materials were collected through a direct qualitative content analysis and analyzed through a multimodal discourse analysis. The results show that there is still a tendency to portray the Sámi based on exoticism. This can spread to different media channels, but there are also discrepancies that hint at a gradual change in how Indigenous populations such as the Sámi are presented. The results of this study show the potential for the use of social media channels such as Instagram for Indigenous entrepreneurs and destination management organizations to educate, attract and entice potential visitors. © 2022 Informa UK Limited, trading as Taylor & Francis Group.